Development of Functional Beverage with Antioxidant Properties using Germinated Red Rice and Tempeh Powder Mixture - Agustinah, Widya; Yuandi, Joshua (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2021)
The objectives of this study were to develop a functional beverage containing Germinated Red Rice (GRR) and tempeh powders and analyze the total soluble phenolic content, phenolics profile, in vitro antioxidant activity, and sensory evaluation. A mixture of GRR and tempeh powder at 1:2, 1:1, and 2:1 w/w ratios were mixed with water at 6% w/v concentration. The total soluble phenolic content and the antioxidant activity of the samples increased significantly (p<0.05) with the increasing level of GRR powder and the decreasing level of tempeh powder, whereas 2:1 w/w ratio of GRR and tempeh powder showed the highest total soluble phenolic content (79.79±12.10 ìg/ml GAE) and in vitro antioxidant activity (68.84±1.56%). However, a control beverage containing only GRR powder and only tempeh powder had the highest and lowest total soluble phenolic content and antioxidant activity, respectively. Ferulic acid was detected in all samples containing GRR, while daidzein was not detected and genistein was only detected in 1:2 and 1:1 sample ratios. All formulated samples in lemongrass sugar solution were accepted by the panelists (score 5 out of 7). In conclusion, GRR was responsible to increase the total soluble phenolic content and antioxidant activity of the beverage. A loss of isoflavone in the tempeh-containing beverage samples suggested that optimizing the dose and processing method were important to achieve the optimum health benefits of the ingredients.